Effects of physical activity on psychological well‐being outcomes in breast cancer survivors from prediagnosis to posttreatment survivorship. Issue 8 (1st June 2018) - Aguiñaga, Susan; Ehlers, Diane K.; Cosman, Josh; Severson, Joan; Kramer, Arthur F.; McAuley, Edward
Abstract: Objective: The purpose of this study was to examine the effects of physical activity from prediagnosis to posttreatment survivorship on the psychological well‐being (PWB) outcomes of fatigue, depression, anxiety, and quality of life (QoL) in breast cancer survivors (BCS). Methods: Participants (N = 387) completed a questionnaire battery by using an iPad‐based platform. Measures included self‐reported PA (before diagnosis and currently) and perceptions of fatigue, depression, anxiety, and QoL. Multivariate analysis of covariance was used to examine differences in PWB among BCS categorized into 1 of 4 physical activity levels: (a) low‐active prediagnosis, low‐active currently ( low‐active maintainers ; n = 128); (b) low‐active prediagnosis, active currently ( increasers ; n = 74); (c) active prediagnosis, low‐active currently ( decreasers ; n = 52); and (d) active prediagnosis, active currently ( high‐active maintainers ; n = 136). Participants were classified as active (≥24 units) or low‐active (<24 units) by using Godin Leisure‐Time Exercise Questionnaire cut‐points for health benefits. Results: Fatigue and depression were lowest, and QoL was highest among women in the high‐active maintainers category, followed by the increasers, low‐active maintainers, and decreasers. No differences in anxiety were observed across categories. Women in the high‐active maintainers category differed significantly in fatigue, depression, and QoL from both low‐active categories (low‐active maintainers and decreasers), P  ≤ .001. Women in the increasers category also differed significantly in fatigue, depression, and QoL from the decreasers, P  ≤ .01. Conclusion: Low physical activity during survivorship was associated with greater fatigue and depression and lower QoL. Implications for cancer survivors: Efforts to help increase or maintain high levels of physical activity may be critical to helping BCS maintain their PWB.